The menstrual cycle may not be limited to the endometrium but also may impact gut permeability. Issue 6 (14th December 2019) - Roomruangwong, Chutima; Carvalho, André F.; Geffard, Michel; Maes, Michael
Abstract: Objective: To examine associations between IgA responses to Gram-negative gut commensal bacteria and peri-menstrual symptoms and sex hormone levels during the menstrual cycle in women with and without premenstrual symptoms. Methods: Forty women aged 18–45 years completed the Daily Record of Severity of Problems (DRSP) during all 28 consecutive days of the menstrual cycle. We assayed, in plasma, IgA responses to six Gram-negative bacteria, that is, Hafnei alvei, Pseudomonas aeruginosa, Morganella morganii, Klebsiella pneumoniae, Pseudomonas putida and Citobacter koseri, progesterone and oestradiol at days 7, 14, 21 and 28 of the menstrual cycle. Results: Significant changes in Δ (actual − 1 week earlier) IgA to lipopolysaccharides (LPS) of the six Gram-negative bacteria during the menstrual cycle were observed with peak IgA levels at T4 (day 28) and lows at T1 or T2 (day 7 or 14). The ΔIgA changes in H. alvei, M. Morganii, P. putida during the menstrual cycle were significantly and positively associated with changes in the total DRSP score, and severity of physio-somatic, anxiety and breast-craving, but not depressive, symptoms. The changes in IgA responses to LPS were largely predicted by changes in progesterone and steady-state levels of progesterone averaged over the luteal phase. Discussion: Menstrual cycle-associated changes in IgA directed against LPS and by inference bacterial translocation may be driven by the effects of progesterone on transcellular, paracellular and vascular pathways (leaky gut) thereby contributing to the severity of physio-somatic and anxiety symptoms as well as fatigue, breast swelling and food cravings.